THE PROGRESS OF THE FIRST SEMESTER STUDENTS IN LISTENING SKILL (Jurnal Bahasa Lingua Scientia, 2010)
This is a report of quantitative study on the development of listening score of the first semester students of English Department. The data are the students’ score of four tasks: task 1, 3, 5, 7, and 9. The data reveal that there 7 students who could consistently improve, secondly consistently up and down improved as 22 students. It can be said that 22 students and the scores of other 22 students are up and down. It could be because of some problems such as having trouble of sounds, not knowing all the words, no understanding fast speech, such as natural native speech, no being able to keep up the native utterance, getting tired after joining other activities.
Keywords: progress; listening skill